2019
DOI: 10.1063/1.5082782
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineering of black phosphorene towards an enhanced polysulfide host and catalyst for lithium-sulfur batteries: A first principles study

Abstract: Although lithium-sulfur (Li-S) batteries are widely regarded as one of the most promising next-generation high energy density storage systems, their large-scale applications are seriously impeded by rapid capacity fading and poor Coulombic efficiency owing to the shuttling of lithium polysulfides (LiPSs) and irreversible discharge product Li2S. Here, by means of first principles calculations, we studied defective black phosphorene (BP) as a host material to realize high-performance Li-S batteries, including St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 54 publications
6
17
0
Order By: Relevance
“…The trend in the increase of the shortest distance with the decrease in the S concentration in LiPSs is correlated with the corresponding binding energies (see Figure ). Similar characteristic changes in bond lengths are also observed in other AMs. ,, Additionally, we analyze intramolecular Li–S bond lengths in LiPSs before and after adsorption and the data are included in Table . We found that the adsorption of the LiPSs on WS 2 causes an increase in the intramolecular Li–S bond length and this increase manifests stronger interactions of LiPSs with WS 2 .…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…The trend in the increase of the shortest distance with the decrease in the S concentration in LiPSs is correlated with the corresponding binding energies (see Figure ). Similar characteristic changes in bond lengths are also observed in other AMs. ,, Additionally, we analyze intramolecular Li–S bond lengths in LiPSs before and after adsorption and the data are included in Table . We found that the adsorption of the LiPSs on WS 2 causes an increase in the intramolecular Li–S bond length and this increase manifests stronger interactions of LiPSs with WS 2 .…”
Section: Resultssupporting
confidence: 61%
“…The structural deformation of the adsorbed LiPS species is apparent, whereas WS 2 retains the structural integrity. The Li atoms in LiPSs remain close to the surface similar to graphene, MoS 2 , TiS 2 , blue phosphorene, Ti 3 C 2 S 2 , and black phosphorene but is in contrast to that seen in the borophene where S atoms remain closer to AMs. The feature of the stereo configurations of the adsorbed LiPSs can be attributed to differences in the net electronegativity values between the AM and the S in the LiPSs.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Incorporating defective 2D materials into sulfur cathodes can prevent the polysulfides from disintegrating and have been widely investigated. Experimental studies and density functional theory (DFT) calculations showed that the defect sites on 2D materials such as nitrogen-doping could prevent Li 2 S n diffusion and dissolution by introducing a strong synergistic effect on their adsorption. Following the effect of structural defects in Li–S batteries, Liu et al . performed a study on a composite of sulfur with three-dimensional porous graphene aerogel (GA) decorated with defect-rich MoS 2 nanosheets.…”
Section: D Materials To Prevent Shuttling Of Polysulfidesmentioning
confidence: 99%